2007
DOI: 10.1002/jcp.20941
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C‐ERK1/2 signal pathway switches glucose depletion‐induced necrosis to apoptosis by regulating superoxide dismutases and suppressing reactive oxygen species production in A549 lung cancer cells

Abstract: Cells typically die by either apoptosis or necrosis. However, the consequences of apoptosis and necrosis are quite different for a whole organism. In the case of apoptosis, the cell content remains packed in the apoptotic bodies that are removed by macrophages, and thereby inflammation does not occur; during necrosis, the cell membrane is ruptured, and the cytosolic constituents are released into the extracellular space provoking inflammation. Recently, inflammation and necrosis have been suggested to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 53 publications
7
99
0
Order By: Relevance
“…Previously, we have shown that metabolic stress induces necrosis and HMGB1 release through mitochondrial ROS production in several cancer cells (10). Here we show that a specific set of cellular proteins including pro-apoptotic molecules p53, caspase-3, and caspase-9 and a pro-autophagic molecule beclin 1 are aggregated in a ROS-dependent manner during GD-induced necrotic cell death.…”
Section: Introductionmentioning
confidence: 51%
See 3 more Smart Citations
“…Previously, we have shown that metabolic stress induces necrosis and HMGB1 release through mitochondrial ROS production in several cancer cells (10). Here we show that a specific set of cellular proteins including pro-apoptotic molecules p53, caspase-3, and caspase-9 and a pro-autophagic molecule beclin 1 are aggregated in a ROS-dependent manner during GD-induced necrotic cell death.…”
Section: Introductionmentioning
confidence: 51%
“…A549, MDA-MB231, and MCF-7 cells were obtained from American Type Culture Collection and maintained in RPMI-1640 or DMEM containing 10% FBS and treated with GD or chemicals as described previously (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5G and H). We have previously shown that in A549 cells, GD was accompanied by release of cytosolic CuZnSOD into extracellular medium, resulting in strong oxidative stress (39). In this regard, aggregation of p53 and HSP27 appears to be closely associated with incurrence of excessive oxidative stress.…”
Section: Heat Shock-activated Akt/pkb and Erk1/2 Pathways Play A Critmentioning
confidence: 89%